The Effect of STAT3 Signal Pathway Activation on Retinopathy of Prematurity - Ren, Jianbing; Jiang, Jingbo; Ou, Weiming; Luo, Xianqiong; Xiang, Jianwen; Liu, Guosheng; Huang, Shuiqing; He, Longkai; Gan, Jiamin; Li, Hongping; Nie, Chuan (Frontiers in Pediatrics, 2021)
Objective: This study aimed to investigate the mechanism, preventive and therapeutic effect of the STAT3 signal pathway on retinopathy of prematurity. Methods: Neonatal SD rats were separated into the hyperoxia and control groups. The level of ferritin in blood on 21d was measured using the ELISA machine and the expression of STAT3 protein and ferritin in the liver determined using RT-PCR, mRNA and western blotting. Subsequently, the number of retinal vessels was observed through HE staining, and the retina of rats obtained under an anatomical microscope. Next, the retinal vessels were labeled with fluorescein lectin to comprehend the ischemic retinal area, vascular branches, and the neovascularization plexus. Consequently, retinal cells were treated with 250 µmol/L cobalt chloride for 72 hours. After adding S3I-201, the level of STAT3 was determined through Western blotting and the proliferation of retinal cells detected using the tetrazolium salt colorimetric assay. Results: The expression of STAT3 protein increased significantly after hyperoxia stimulation, and the expression of ferritin mRNA in the hyperoxia group was significantly higher than that in the control group. After treatment with cobalt chloride, the proliferation of retinal cells was inhibited, expression of STAT3 increased, and no significant difference noted in VEGF mRNA. After adding its inhibitor S3I-201, the expression of STAT3 and VEGF mRNA reduced. Conclusion: The activation of the STAT3 signal pathway increases the expression of ferritin contributing to the pathogenesis of ROP. S3I-201 can inhibit the expression of STAT3 and VEGF mRNA level, thereby prevent and treat ROP.